Teknik Pembuatan Gelungan Tari Topeng Panca Di Sanggar Seni Citra Kara - Gus Adi, Kadek Bagus Adi Setiawan; Suparta , I Made; Agung Jaya CK, I Gusti Ngurah (Pusat Penerbitan LP2MPP ISI Denpasar, 2024)
The internship/work practice activities of the Independent Learning Independent Campus program were carried out by the author in Batuan Village, Sukawati District, Gianyar Regency, where most of the population is engaged in the field of art, both fine arts and performing arts. All forms of art have existed since ancient times and have been passed down from generation to generation. Citra Kara Art Studio is a studio located in Batuan Village, which produces mask art products and skin inlays, so it is considered to be able to provide new experience and knowledge about how and techniques of skin carving in making panca mask crown . Knowledge of tools and materials such as the use of chisels, the use of modern technology to speed up the assembly process. Knowledge of the type of chisel and the use of materials as well as the application of technology to accelerate the process of making products, especially the crown of the panca mask. From an academic point of view, the author gained knowledge such as the types of Balinese dance crown, the parts contained in , and the ornaments applied to the crown. The method used in the Independent Learning Independent Campus activity uses method tracing, observation, interviews, literature studies, and documentation. The headdress or crown that the author makes is in the form of a girdle of the panca mask or pajegan which is a wali or sacred dance that is staged at every religious event and has different characters such as, a gentle and weak character, a person with a hard character, a parent character, a wise character, and a person with a funny character